Determinants of Interest Using QRIS as a Payment Technology For E-Wallet by Z Generation in Indonesia - Mareta, Yossi; Meiryani, Meiryani (Syntax Literate, 2023)
In the midst of the rapid growth of financial technology companies that act as payment system service providers (PJSP) in Indonesia continue to innovate,the Quick Response Code Indonesian Standard(QRIS)is present as a solution to implement innovations in payment systems offered by these fintech companies. This study aims to identify the factors that influence the interest of Gen Z in using the QRIS payment system in the e-wallet. This study used systematic literature review. The result of the study shows that perceived ease of use, perceived usefulness, trust, social influence, dan promotion have a positive, while risk has a negative influence on the interest of Gen Z in Indonesia in using the QRIS payment system in E-wallet.